Desenvolvimento de minissensores de filme de bismuto para a determinação voltamétrica in loco de atrazina, diquat e paraquat em águas naturais - Figueiredo Filho, Luiz Carlos Soares de (2011)
The development of bismuth film electrodes (BiFE) and minissensors/BiFE for application to the development of electroanalytical procedures for determination of atrazine, Diquat and Paraquat using voltammetric techniques as square wave (SWV) and differential pulse (DPV) is reported in this work. It was chosen to combine the working electrode (BiFE), pseudo-reference (silver glue) and counter (copper) in the same bracket for easily locomotion of the electrochemical system for field analysis. Copper plates of printed circuit were used as substrate and nail polish was used as an electrical insulator to limit the active area. Thus it was possible to make a minissensor with low cost. For the first procedure developed it was determined atrazine in natural waters using BiFE and DPV after the optimization of experimental conditions was obtained an analytical curve linearity for the range from 6.6 x 10-7 to 2.0 x 10-5 mol L-1, with a limit of detection of 1.4 x 10-7 mol L-1. Subsequently, parameters of the SWV technique for determination of Diquat in water samples were studied using BiFE and minissensor/BiFE and the linear correlation was obtained for a concentration range from 1.9 to 5.6 x 10-7 x 10-6 mol L-1 and from 1.9 x 10-7 to 9.3 x 10-6 mol L-1 respectively, and the limit of detection obtained were 8.7 x 10-8 mol L-1 and 8.9 x 10-8 mol L-1. Finally a procedure was developed for the determination of Paraquat using BiFE and minissensor/BiFE by DPV. For the BiFE a linear relationship was obtained for the concentration range from 6.6 x 10-7 to 4.8 x 10-5 mol L-1, with a limit of detection of 9.3 x 10-8 mol L-1. After being selected the best experimental conditions for minissensor/BiFE, it responded to a linear concentration range from 6.6 x 10-8 to 3.9 x 10-6 mol L-1 with a limit of detection of 1,2 x 10-8 mol L-1.